An analytic framework to assess future electricity options in Kosovo. (13th October 2016) - Kittner, Noah; Dimco, Hilda; Azemi, Visar; Tairyan, Evgenia; Kammen, Daniel M
Abstract: We have developed an analytic platform to analyze the electricity options, costs, and impacts for Kosovo, a nation that is a critical part of the debate over centralized versus distributed electricity generation and the role of fossil fuels versus cleaner electricity options to meet growing demands for power. We find that a range of alternatives exists to meet present supply constraints all at a lower cost than constructing a proposed 600 MW coal plant. The options include energy efficiency measures, combinations of solar PV, wind, hydropower, and biomass, and the introduction of natural gas. A 30 EUR ton –1 shadow price on CO2 increases costs of coal generation by at least 330 million EUR. The results indicate that financing a new coal plant is the most expensive pathway to meet future electricity demand.